ALIH AKSARA DAN ALIH BAHASA TEKS INI SYAIR LAMPUNG KARAM ADANYA - Kurnia, Rahmat Rizki; Nurizzati, Nurizzati; Nst., Muhammad Ismail (Jurnal Bahasa dan Sastra, 2018)
This article is written to: (a) present the description of the text Ini Syair Lampung Karam Adanya, (b) present the translation of the text texts Ini Syair Lampung Karam Adanya, and (c) presents the change of the text language Ini Syair Lampung Karam Adanya. This research is a philology research. The object of this research is text Ini Syair Lampung Karam Adanya. The method used in this research is four steps. They are a collection of data, describing text, translations, and language changes. The result of this research is to present a text which can be read by society nowadays this text story Ini Syair Lampung Karam Adanya.Keywords: change of script, language transfer, text, philology